PERFORMANCE ANALYSIS OF MOROTAI ISLAND REGENCY IN THE REGIONAL REGULATION MECHANISM - Sri Ka’bah (Peneliti.net, 2019)
The results of this study indicate that the performance of the Morotai Island Regency Government in the mechanism of drafting local regulations ranging from planning to the dissemination of these Perda has been implemented well, but the drafting of the draft of this regional regulation which drafted was from the executive and the Draft Regulations proposed and carried out the discussion is not based on Prolegda. Of the total Ranperda proposed by the regional government starting from 2010-2014 as many as 32, the Regional Regulation is the Regional Government Initiative, while from the Morotai Regency DPRD itself is absent. The regional bylaws submitted by the Regional Government to the Morotai Regency DPRD have all been accepted and none of them have been rejected by the DPRD, and even these Regulations have become the current Morotai Regency Regulations. Factors influencing the performance of the Morotai Island Regency DPRD in the implementation of the making of this regional regulation include: Human resources, data or information, and experience by the Morotai Island DPRD itself.